Heavy Metal Pollution Assessment in Lake Rinconada in the Southern Andes, Peru - Salas Mercado, Dante (2023)
The study was conducted in Lake Rinconada, a glacial lake affected by artisanal and small-scale gold mining activities in the southern Andes in Peru. The objectives of the study were to investigate the spatial distribution of heavy metals (As, Cu, Hg, Pb and Zn) in water and sediments and to assess the degree of metal pollution and ecological risk using the geoaccumulation and potential ecological risk indexes. The concentrations of As and Hg in sediments from Lake Rinconada exceeded the Canadian sediment quality regulations, whereas the concentrations of As, Hg and Pb in water and sediments from the mining-affected tributary, Lunar de Oro River exceeded the Peruvian and Canadian guidelines for water and sediments quality respectively. According to the geoaccumulation and potential ecological risk indexes, Lake Rinconada is extremely polluted by As and Hg, and the pollution is mostly concentrated in the northern part of the lake, where the mining-affected Lunar de Oro River flows into the lake. Concentrations of Pb are also high in the northern part of the lake, suggesting that the nearby gold mining town is a source of pollution. The results of this study allows to report that Lake Rinconada is completely deteriorated.